Impact of Logging Bans on Deforestation: Evidence from the Vietnam-Laos Border - Dela Pena, John Luigi. (Tufts University. Tisch Library., 2023)
Thesis (M.S.)--Tufts University, 2023.; Submitted to the Dept. of Economics.; Advisor: Ujjayant Chakravorty.; Committee: Kyle Emerick.; Keywords: Economics, Climate change, and Agriculture economics.